Effects of Food Types, Frying Frequency, and Frying Temperature on 3-Monochloropropane-1,2-diol Esters and Glycidyl Esters Content in Palm Oil during Frying - Jinglin Zhang; Wendi Zhang; Yuanzheng Zhang; Mingquan Huang; Baoguo Sun (Foods, 2021)
3-Monochloropropanediol esters (3-MCPDE) and glycidyl esters (GE) have high toxicity and have drawn global attention because of their widespread occurrence in refined oils and oil-based foods. In this study, the effects of food type (potato chips and chicken breasts), frying frequency, and frying temperature on the formation of 3-MCPDE and GE in palm oil (PO) were investigated. The results showed that 3-MCPDE was formed easier in chicken breasts than potato chips. The GE content decreased in PO after it was used for frying potato chips and chicken breasts with or without NaCl. Frying frequency was an influencing factor in the formation of 3-MCPDE and the decrease in GE in PO. Frying temperature was positively correlated with GE degradation, while it had a bidirectional effect on the formation of 3-MCPDE. The formation kinetic equations indicated that 3-MCPDE and GE followed zero-order reactions in PO. The estimated activation energy (Ea) of 1,2-bis-palmitoyl-3-chloropropanediol (Pa-Pa, 41.05 kJ/mol) was lower than those of the other three types of 3-MCPDE; this is the first theoretical explanation for why PO contains more 3-MCPD than other edible oils. Among GEs, glycidyl oleate (Li-GE) was degraded more readily than other GEs.